Social marginalization, gender-based violence, and binge drinking among transgender women in Cambodia. (1st February 2020) - Yi, Siyan; Chann, Navy; Chhoun, Pheak; Tuot, Sovannary; Mun, Phalkun; Brody, Carinne
Highlights: Social marginalization and gender-based violence may lead to behavioral risks. Prevalence of binge drinking among transgender in Cambodia was 43.3 %. Marginalization, gender-based violence, and alcohol abuse are correlated. Occupational health interventions among transgender women are needed. Abstract: Background: Transgender women experience disproportionate social stigma that may lead to behavioral risks and poor psychological wellbeing. This study examines social and behavioral factors associated with binge drinking among transgender women in Cambodia. Methods: A cross-sectional survey was conducted in 2016 among 1039 transgender women recruited from 13 provinces using the Respondent Driven Sampling method. A structured questionnaire was used for face-to-face interviews. Weighted multivariable logistic regression analysis was conducted to identify risk factors associated with binge drinking. Results: The prevalence of binge drinking was 43.3 %. After adjustment, the odds of binge drinking were significantly higher among participants in the age group of 25–34 compared to those in the age group of 18–24 and lower among participants in job categories such as hairdresser or beautician, office workers, and self-employed compared to those who were unemployed. The odds of binge drinking were significantly higher in participants who dropped out of school and thought it was because of their transgender identity, had transactional sex in the past three months, used amphetamine-type stimulants in the past three months, and reported experience of verbal abuse by family members during childhood. Regarding mental health, the odds of binge drinking were significantly lower among participants who had depressive symptoms over the past week. Conclusions: These findings highlight the intersections between social marginalization, gender-based violence, HIV risks, and alcohol abuse. We recommend further exploration of the structural factors that may be modifiable through workplace policies or occupational health interventions among transgender women.